Jelajah Desa, Televisi Lokal dan Potensi Pariwisata Kota Jombang - Wildan Isfaguwanto; Nikmah Suryandari (Institut Pertanian Bogor, 2022)
This paper seeks to discuss local television content in Jombang and tourism potential in Jombang City. The research was conducted at Ringin Corong Television (RCTV) with qualitative descriptive research methods. The object of research is this Village Cruising Event is an event that seeks to raise various information about tourism in the Jombang area. This type of research is qualitative descriptive. Data collection techniques using observation, interviews and documentation. The results showed that the Village Cruising event tried to lift the potential in villages such as livestock, agriculture, to natural tourism. Through the Village Cruising event program, it is expected to increase the promotion of tourism potential in the city of Jombang. RCTV also promotes its business through social media which can indirectly increase the range of information about RCTV and potential in Jombang City.